2011
DOI: 10.1063/1.3664781
|View full text |Cite
|
Sign up to set email alerts
|

Bias application hard x-ray photoelectron spectroscopy study of forming process of Cu/HfO2/Pt resistive random access memory structure

Abstract: The forming process of Cu/HfO2/Pt, which is an oxide based resistive random access memory (ReRAM), structure that exhibited resistance switching behavior at a voltage of 1.3 V was investigated by hard x-ray photoelectron spectroscopy under bias operation. A bias application to the structure reduced the Cu2O bonding state at the interface and the intensity ratio of Cu 2p3/2/Hf 3d5/2, providing the evidence of Cu2O reduction and Cu diffusion into the HfO2 layer. We directly observed Cu diffusion at the Cu/HfO2 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
44
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 26 publications
0
44
0
Order By: Relevance
“…Additionally, it has been observed that Cu filament always formed in the RRAM with HfO 2 dielectric when copper served as positive electrode. [35][36][37] Besides, through investigating the resistive switching characteristic of Pt/HfO 2 /n-Si device, there is no obvious rectifying effect, which is quite different with Cu/HfO 2 /n-Si device. Since there is oxygen vacancy filament formed in the Pt/HfO 2 /n-Si device, it should be copper filament caused the difference of rectifying effect in Cu/HfO 2 /n-Si device.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it has been observed that Cu filament always formed in the RRAM with HfO 2 dielectric when copper served as positive electrode. [35][36][37] Besides, through investigating the resistive switching characteristic of Pt/HfO 2 /n-Si device, there is no obvious rectifying effect, which is quite different with Cu/HfO 2 /n-Si device. Since there is oxygen vacancy filament formed in the Pt/HfO 2 /n-Si device, it should be copper filament caused the difference of rectifying effect in Cu/HfO 2 /n-Si device.…”
Section: Resultsmentioning
confidence: 99%
“…Generally speaking, there are metal CF 27,35-37 and oxygen vacancy CF [38][39][40] in the binary oxide dielectric such as HfO 2 film. Many studies have been reported that active electrodes such as Ag 4,41 and Cu [35][36][37] tends to migrate and form CF connecting with counter electrodes, playing an important role in resistive switching process. Additionally, it has been observed that Cu filament always formed in the RRAM with HfO 2 dielectric when copper served as positive electrode.…”
Section: Resultsmentioning
confidence: 99%
“…Hard x-ray photoelectron spectroscopy (HAXPES) is a powerful synchrotron method to study deeply buried interfaces in a non-destructive way. 15 Although this technique has already shown its high potential to study the RS phenomenon in NiObased RRAM device 14 and Cu/HfO 2 -based RRAM device, 16 the electroforming step, as a prerequisite of the RS, is not fully explained, especially not for the HfO 2 -based system, which is gaining increased research interest as suitable candidate to enable future RRAM technologies. 17 Hence, in this work, we focus on understanding the chemical and electronic modifications that occur during this first electroforming process on CMOS-compatible Ti/HfO 2 /TiN RRAM cells.…”
mentioning
confidence: 99%
“…It is defined as a two-terminal element that provides the missing constitutive relationship between charge and flux. Ignited by the successful fabrication of a real nanoscale memristor by HP Labs in 2008 [2], tremendous research has been devoted to explore memristor-based potential applications in such areas as resistive random access memory (RRAM) [3,4], analog circuits [5,6], digital circuits [7,8], chaotic circuits [9,10], and neural networks [11,12]. Although memristor has many potential applications, it is not available as a universal electronic device for ordinary researchers.…”
Section: Introductionmentioning
confidence: 99%